Two new endangered species of Anomaloglossus (Anura: Aromobatidae) from Roraima State, northern Brazil - Fouquet, Antoine; Souza, Sergio Marques; Nunes, Pedro M. Sales; Kok, Philippe J. R.; Curcio, Felipe Franco; de Carvalho, Celso Morato; Grant, Taran; Rodrigues, Miguel Trefaut (Zootaxa, 2015)
We describe two new species of Anomaloglossus from Roraima State, Brazil, that are likely endemic to single mountains currently isolated among lowland forest and savanna ecosystems. The first species, Anomaloglossus tepequem sp. nov. was collected in 1986 and 1992 along a single stream at >500 m elevation on a tepui-like mountain named Tepequém, but was not detected during recent investigations. It is mainly diagnosed from other Anomaloglossus species by its well developed foot webbing, immaculate cream abdomen colouration and small body size (males: 18.2–20.1 mm, females: 21.7–24.5). The second species, Anomaloglossus apiau sp. nov. was found along several streams between 500 and 1400 m elevation on Serra do Apiaú, and is mainly diagnosed from congeners by its weakly webbed feet, males with swollen third finger and ventrolateral stripe formed by white dots, and its advertisement call; a long trill (up to almost 40 s) consisting of pairs of very short pulses. The discovery of these two apparently microendemic species suggests that additional Anomaloglossus species remain to be described in the Guiana Shield. Both species should be considered critically endangered given their seemingly reduced range size, association with highland habitat, and the anthropogenic pressure they currently face.